PENGARUH MODAL INTELEKTUAL, LEVERAGE DAN KAPASITAS OPERASI TERHADAP PROFITABILITAS - Tita Yuliyanti; Wulandari Agustiningsih (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Profitability is very important for the company for its survival. The purpose of this study is to determine determinants such as intellectual capital, leverage, and operating capacity on the profitability of consumer goods sector companies listed on the Indonesia Stock Exchange in 2018-2022. This type of research is causality and the research method uses quantitative methods obtained from secondary data. The statistical tool in this research uses STATA. The sampling technique used purposive sampling and obtained as many as 51 companies that met the criteria from a total population of 22 companies with a research period of 5 years, so that 110 sample data were obtained. This study utilizes a multiple linear regression analysis model. The results of the study show that intellectual capital, leverage, and operating capacity simultaneously affect profitability. Empirically, the role of intellectual capital, leverage and operating capacity in increasing the profitability of companies in the consumer goods subsector. Studies on the consumer goods sub-sector show that intellectual capital has a positive effect on profitability, leverage has a positive impact on profitability and operating capacity has a positive effect on profitability.